Potencial antioxidante dos extratos de Moringa oleífera Lamark em sistemas lipídicos de baixa estabilidade oxidativa - Batista, Jaqueline Azevedo Nascimento (2013)
The species Moringa oleifera Lamarck is a perennial and drought-tolerant plant cultivated as ornamental and medicinal plant. In this study, ethanolic extracts of leaves, flowers, and seed pods of this plant were evaluated for their protective effect against soybean and fish oil oxidation. For this, total extractable phenolics (TEP) were determined by Folin-Ciocalteau method, as well as the antioxidant potential, using the DPPH radical scavenging activity method (RSA-DPPH), iron power reduction (FRAP) and β-carotene/ linoleic acid system. The thermal stability of extracts was measured by thermal analysis (TG / DTA) and the antioxidant effect on soybean and fish oils was investigated by the Rancimat method, pressurized differential scanning calorimetry (P-DSC) and accelerated storage test. The preliminary toxicity assessment of extracts was performed using Artemia salina larvae. The TEP levels in extracts of leaves, flowers and seed pods were (53.69 ± 1.00), (45.85 ± 1.71), (41.75 ± 3.35) and (8.06 ± 0.47) mg GAE / g of extract, respectively. In tests to determine the antioxidant capacity, extract from leaves showed better RSA-DPPH and FRAP and also higher antioxidant activity in the β-carotene/ linoleic acid system. In the thermal stability evaluation, extract from leaves was also more stable than the other extracts. In tests to evaluate the antioxidant effect of extracts, it was found that extract from leaves was more efficient in both oils in Rancimat and P-DSC methods with protective effect equivalent to synthetic antioxidant BHT in soybean oil using the Rancimat method. In the accelerated storage test, it was found that after 16 days of storage, extract from leaves was the most effective in inhibiting the formation of oxidation products in both oils, being more effective than BHT and TBHQ in fish oil. The results of the preliminary toxicity assessment showed low toxicity, suggesting that the extracts may be consumed without health damage. These results suggest that the ethanolic extract of moringa leaves has efficient protective effect when applied to lipid systems of low oxidative stability and could be an alternative source of potential application in the oils and fats industry.